What Drowns the Flowers in Your Mouth A Memoir of Brotherhood - González, Rigoberto (The University of Wisconsin Press, 2013)
Burdened by poverty, illiteracy, and vulnerability as Mexican immigrants to California's Coachella Valley, three generations of González men turn to vices or withdraw into depression. As brothers Rigoberto and Alex grow to manhood, they are haunted by the traumas of their mother's early death, their lonely youth, their father's desertion, and their grandfather's invective. Rigoberto's success in escaping-first to college and then by becoming a writer-is blighted by his struggles with alcohol and abusive relationships, while Alex contends with difficult family relations, his own rocky marriage, and fatherhood. Descending into a dark emotional space that compromises their mental and physical health, the brothers eventually find hope in aiding each other. This is an honest and revealing window into the complexities of Latino masculinity, the private lives of men, and the ways they build strength under the weight of grief, loss, and despair.